Model-Based Control of a Turbocharged Diesel Engine with High- and Low-Pressure Exhaust Gas: - Mrosek, Matthias Patrick Alexander (VDI Verlag, 2017)
“Model-Based Control of a Turbocharged Diesel Engine with High- and Low-Pressure Exhaust Gas Recirculation“ presents the complete scope for a model-based control design with regard to the control objective dynamical driving cycle emissions. A semi-physical air path model delivers system properties of the controlled system. Experimental models for stationary and dynamical engine raw emissions are the base for stationary and dynamical optimisations of emissions and engine torque and allow to motivate deviations between stationary and dynamical emission formation. The control concept directly incorporates semi-physical relationships and model parameters of the air path model for control of HP-EGR, LP-EGR and charging pressure. The control performance is rated with quantified stationary and dynamical contributions to the overall driving cycle emissions. All models and control methods have been experimentally parameterised and validated at an engine test bench....